Cardiac scintigraphy-centered diagnostic process in transthyretin cardiac amyloidosis - Ilknur Ak Sivrikoz; Yüksel Çavuşoğlu (KARE Publishing, 2020)
Cardiac amyloidosis (CA) is a progressive infiltrative cardiomyopathy. Amyloid fibrils in the form of misfolded endogenous proteins accumulate in the heart, as well as the kidneys, liver, and gastrointestinal tract. The most common forms of CA are transthyretin (TTR) and immunoglobulin light chain amyloidosis (AL). CA has long been thought to be a rare disease. However, recent reports have suggested that 13% of heart failure patients with a preserved ejection fraction and 16% of advanced-age patients with severe aortic stenosis have TTR-CA. Patients with TTR-CA have a poor prognosis, with a median survival of 2-4 years; however, early diagnosis and novel therapeutic options have been shown to significantly improve the prognosis. Scintigraphy using bone isotopes is considered a highly reliable and easy-to-use method in the diagnosis of TTR-CA. This is a review of the role of scintigraphic imaging with technetium-99m- labeled bisphosphonates in the diagnostic work-up process of TTR-CA and the applicable protocols.